IN VITRO ANTIOXIDANT AND IN VIVO ANTI-INFLAMMATORY ACTIVITY OF THE AERIAL PART OF BLUMEA ERIANTHA DC - Tambewagh, Urmila U.; Rojatkar, Supada Rambhau (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: Objective of the present study was to carry out in vivo anti-inflammatory and in vitro antioxidant activity of methanol extract of aerial part of the Blumea eriantha DC belonging to family Asteraceae. Methods: The shade dried aerial part of B. eriantha (0.5 kg) was powdered and extracted with methanol (1.5 x 3L) at room temperature (24h x 3). After filtration combined all the three extracts and were concentrated on rotary evaporator under reduced pressure at 40 Â°C, thereby providing crude methanol extract which was subsequently employed for further studies. Anti-inflammatory effect was studied by carrageenan-induced paw edema model in rats at dose level 100, 200, and 400 mg/kg. Acute oral toxicity study and in vitro antioxidant potential of the extract was also studied. The in vitro antioxidant activity of methanol extract of aerial part of Blumea eriantha DC was evaluated against 1,1-diphenyl-2-picrylhydrazyl (DPPH), hydrogen peroxide (H2O2) and hydroxyl (OH) radicalscavenging and reducing power assays. Results: The results indicate that methanol extract of Blumea eriantha (BEME, 400 mg/kg) exhibited significant inhibition (p<0.001) of increase in paw edema at 5th h. IC50 value of BEME showed significant antioxidant activity. The extract exhibits promising free radical scavenging effect of DPPH, H2O2, OH and reducing power in a dose-dependent manner up to 100Âµg/ml concentration while the reference standard Ascorbic acid demonstrated more scavenging potential than the methanol extract of Blumea eriantha The methanol extract was found to be safe at the dose of 2000 mg/kg. Conclusion: The results of the experimental study confirmed that methanol extract of Blumea eriantha DC possesses significant anti-inflammatory and antioxidant activity.